Locus and gene search in three disorders - Hazan, Renin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Identification of genetic defects associated with hereditary diseases is important in understanding cellular mechanisms and molecular etiology of diseases, developing diagnostic tests and novel therapeutic techniques. In this study, genetic analysis was performed to map genetic loci and identify the responsible gene in three families afflicted with different autosomal recessive hereditary diseases: azoospermia, diabetes mellitus type 1, microhydranencephaly. Gene localizations involved genome scan followed by fine mapping. Localization studies were completed for all diseases, while candidate gene approach led to the identification of the gene responsible for one of them. Azoospermia is absence of detectable level of spermatozoa in the semen. In a consanguinous family with three affected sibs, the condition was mapped to 17pter-13.1 and 14q11.2-12. Seven candidate genes were analyzed, and the disease gene was identified as SPAG7, a homolog of fox sperm acrosomal protein. The mutation R136W resided in a 13 amino acid-cluster conserved in all mammals. Microhydranencephaly is a rare developmental defect of the brain, where the unusual association of microcephaly and hydranencephaly is observed. In a nuclear family with two affected sibs, genetic linkage analysis and haplotype construction followed by verification with microsatellite markers led to the identification of several candidate loci, with the strongest one at 6p25.3-p25.2. Five candidate genes were analyzed but no mutation was found. Diabetes Mellitus Type 1 exhibits complex inheritance. A consanguineous family having four of thirteen sibs affected suggested autosomal recessive inheritance. The strongest candidate locus identified by using genome scan data was 8q24.23. The locus harbors gene FAM135B.
Keywords: Medical genetics.; Human genetics.